Medicine : stem cells, genes, and super-beams - Rooney, Anne. (Chicago : Heinemann, 2006)
Examines the advancements in science and technology and discusses some of the ethical issues involved in things such as drug testing, euthanasia, genetic engineering, abortion, and much more.
The big picture -- Stem cells -- Working with genes -- Man and machine -- Super-beams -- New parts for old -- Superbugs and superdrugs.
Includes bibliographical references (p. 55) and index.
Library Media Connection.
7.2
5-8
Keywords: Medical technology -- Juvenile literature; Medicine -- Juvenile literature; Medicine -- History -- Juvenile literature; Medical technology; Medicine; Medicine -- History; Medical technology; Medicine; Medicine -- History